THE EFFECT OF LOCAL TAXES, GENERAL ALLOCATION FUNDS AND SPECIAL ALLOCATION FUND FOR ECONOMIC GROWTH IN ACEH PROVINCE - Intan Maghfirah; Devi Andriyani (Journal of Malikussaleh Public Economics, 2022)
The study examined the effect of local taxes, general allocation funds, and special allocation funds on economic growth in Aceh Province during 2016-2020. This study used secondary data for 5 years. This study used the panel data regression method with 115 observations from 23 selected samples. The Fixed Effect results partially indicated that Local Taxes did not significantly influence Economic Growth, General Allocation Funds did not significantly influence Economic Growth, and Special Allocation Funds positively and significantly influenced Economic Growth. Simultaneously, Regional Taxes, General Allocation Funds, and Special Allocation Funds influenced Economic Growth in 23 Regencies/Cities of Aceh Province during 2016-2020.